2010
DOI: 10.1007/s00726-010-0736-7
|View full text |Cite
|
Sign up to set email alerts
|

A pro-survival effect of polyamine depletion on norepinephrine-mediated apoptosis in cardiac cells: role of signaling enzymes

Abstract: Recent studies report that the primary transmitter of sympathetic nervous system norepinephrine (NE), which is actively produced in failing human heart, is able to induce apoptosis of rat cardiomyocytes. Apoptotic cell death of cardiomyocytes is involved in several cardiovascular diseases including ischemia, hypertrophy and heart failure, therefore representing a potential therapeutic target. The natural occurring polyamines, putrescine, spermidine and spermine, are biogenic amines involved in many cellular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Previous studies reported that acute taurine co-treatment or pre-treatment prevents ethanol-induced changes in acetylcholinesterase activity and ethanol-induced release of dopamine (Rosemberg et al 2010;Ericson et al 2010). Imbalance of some neurotransmitters, such as dopamine (Radl et al 2011;Aslan et al 2011), norepinephrine (Cetrullo et al 2011;LaJevic et al 2011) could be directly or indirectly related to apoptosis event, which is consistent with the results of western blot results Bcl-2 and caspase-3 in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies reported that acute taurine co-treatment or pre-treatment prevents ethanol-induced changes in acetylcholinesterase activity and ethanol-induced release of dopamine (Rosemberg et al 2010;Ericson et al 2010). Imbalance of some neurotransmitters, such as dopamine (Radl et al 2011;Aslan et al 2011), norepinephrine (Cetrullo et al 2011;LaJevic et al 2011) could be directly or indirectly related to apoptosis event, which is consistent with the results of western blot results Bcl-2 and caspase-3 in this study.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with recent papers reporting a similar protective effect of DFMO against apoptosis in cardiac cells treated with aldosterone, or when cells were exposed to simulated ischemia conditions [20,21]. A study investigating the effects of polyamine depletion on norepinephrine mediated apoptosis in rat neonatal cardiomyocytes and H 9 C 2 cardiomyoblasts demonstrated that DFMO had a pro-survival effect that was mediated through a specific network of phosphatases and kinases [22]. …”
Section: Discussionsupporting
confidence: 81%
“…Some recent studies support a pro-apoptotic effect of polyamines. Among them, a study revealed that cell apoptosis induced by norepinephrine in rat cardiomyocytes is mediated by an early induction of ODC, and that these effects are prevented by DFMO [55]. These authors also revealed that the pro-apoptotic effect of polyamines is mediated by the involvement of AMP-activated protein kinase, AKT and p38 mitogen-activated protein kinases.…”
Section: Polyamines and Apoptosismentioning
confidence: 89%